Multiple Environmental Signaling Pathways Control the Differentiation of RORγt-Expressing Regulatory T Cells - Hussein, Hind; Denanglaire, Sébastien; Van Gool, Frédéric; Azouz, Abdulkader; Ajouaou, Yousra; El-Khatib, Hana; Oldenhove, Guillaume; Leo, Oberdan; Andris, Fabienne (Frontiers in Immunology, 2020)
RORγt-expressing Tregs form a specialized subset of intestinal CD4+ Foxp3+ cells which is essential to maintain gut homeostasis and tolerance to commensal microbiota. Recently, c-Maf emerged as a critical factor in the regulation of RORγt expression in Tregs. However, aside from c-Maf signaling, the signaling pathways involved in the differentiation of RORγt+ Tregs and their possible interplay with c-Maf in this process are largely unknown. We show that RORγt+ Treg development is controlled by positive as well as negative signals. Along with c-Maf signaling, signals derived from a complex microbiota, as well as IL-6/STAT3- and TGF-beta-derived signals act in favor of RORγt+ Treg development. Ectopic expression of c-Maf did not rescue RORγt expression in STAT3-deficient Tregs, indicating the presence of additional effectors downstream of STAT3. Moreover, we show that an inflammatory IFN-γ/STAT1 signaling pathway acts as a negative regulator of RORγt+ Treg differentiation in a c-Maf independent fashion. These data thus argue for a complex integrative signaling network that finely tunes RORγt expression in Tregs. The finding that type 1 inflammation impedes RORγt+ Treg development even in the presence of an active IL-6/STAT3 pathway further suggests a dominant negative effect of STAT1 over STAT3 in this process.